Effect of heating spacing on deformation distribution of line heating process - Han, Xiaoshuang (2021)
Ship hull plate forming with line heating technique is an important process in the shipbuilding industry. An automatic line heating control system needs an accurate database of various processing parameters. In this study, a numerical model, calibrated and verified using experiment results, was used to study the deformation distribution of a plate corresponding to different heating line spacing. This paper presents the results based on a single-torch and multiple-torch process. The deformation distributions in the heating and nonheating regions were analyzed. The impacts of coupling effect among heating lines were deliberated.